Radial extracorporeal shockwave treatment compared with supervised exercises in patients with subacromial pain syndrome: single blind randomised study - Engebretsen, Kaia (BMJ Publishing Group Ltd., 2009)
Objective To compare the effectiveness of radial extracorporeal shockwave treatment with that of supervised exercises in patients with shoulder pain. Design Single blind randomised study. Setting Outpatient clinic of physical medicine and rehabilitation department in Oslo, Norway. Participants 104 patients with subacromial shoulder pain lasting at least three months. Interventions Radial extracorporeal shockwave treatment: one session weekly for four to six weeks. Supervised exercises: two 45 minute sessions weekly for up to 12 weeks. Primary outcome measure Shoulder pain and disability index. Results A treatment effect in favour of supervised exercises at 6, 12, and 18 weeks was found. The adjusted treatment effect was −8.4 (95% confidence interval −16.5 to −0.6) points. A significantly higher proportion of patients in the group treated with supervised exercises improved—odds ratio 3.2 (1.3 to 7.8). More patients in the shockwave treatment group had additional treatment between 12 and 18 weeks—odds ratio 5.5 (1.3 to 26.4). Conclusion Supervised exercises were more effective than radial extracorporeal shockwave treatment for short term improvement in patients with subacromial shoulder pain. Trial registration Clinical trials NCT00653081.